Dynamic rupture of metal sheet subjected to laser irradiation and tangential subsonic airflow. Issue 4 (July 2018) - Xing, Xiaodong; Ma, Te; Wang, Ruixing; Cao, Chenyu; Song, Hongwei; Huang, Chenguang
ABSTRACT: To reproduce the premature rupture process of metal sheet subjected to laser irradiation with subsonic airflow, which is an interesting phenomenon observed in the experiments given by Lawrence Livermore National Laboratory, a coupled numerical model considering the interaction and evolution of metal elastoplastic deformation and aerodynamic pressure profile is presented. With the thermal elastoplastic constitutive relationship and failure criterion, the simulated failure modes and dynamic rupture process are basically consistent with the experimental results, indicating plastic flow and multiple fracturing is the main failure mechanism. Compared with the case of non-airflow, subsonic airflow not only accelerates deformation, but also turns the bugle deformation, plastic strain and rupture mode into asymmetric. Graphical Abstract: To reproduce the premature rupture process of metal sheet subjected to laser irradiation with subsonic airflow, which is an interesting phenomenon observed in the experiments given by Lawrence Livermore National Laboratory, a coupled numerical model considering the interaction and evolution of metal elastoplastic deformation and aerodynamic pressure profile is presented. With the thermal elastoplastic constitutive relationship and failure criterion, the simulated failure modes and dynamic rupture process are basically consistent with the experimental results, indicating plastic flow and multiple fracturing is the main failure mechanism. Compared with the case of non-airflow, subsonic airflow not only accelerates deformation, but also turns the bugle deformation, plastic strain and rupture mode into asymmetric.